Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have this heat equation:

$u_t = 9u_{xx} - 7u + f(x,t),$

$f(x,t) = 1; 0 < x < l; 0 < t < T $

$u(x,0) = 6x^2 - 5x +2$

$u(0,t) = 3t + 2$

$u(l,t) = t + 3$

$l = 1$

My problem is that I know how to solve when IC and BC are zeros. Maybe someone knows (or can point me to) a detailed method to transform(?) my equation and what to do then?
Thank you very much.

share|improve this question

2 Answers 2

up vote 1 down vote accepted

Find any function $h(x,t)$ such that $h(0,t)=u(0,t)$ and $h(l,t)=u(l,t)$. Then make the change of variables $u=v+h$. This will give you an equation for $v$ with homogeneous boundary conditions (but a different initial value $v(x,0)$).

share|improve this answer
    
Amusing that you collected a downvote and an acceptance. That should be worth a badge. I can solve one problem with an upvote. –  Ross Millikan Oct 20 '12 at 3:12
    
@RossMillikan This already happened, also in a question about separation of variables in PDE's. –  Julián Aguirre Oct 20 '12 at 8:18

Approach $1$:

Let $u(x,t)=U(x,t)+\dfrac{1}{7}$ ,

Then $u_t(x,t)=U_t(x,t)$

$u_x(x,t)=U_x(x,t)$

$u_{xx}(x,t)=U_{xx}(x,t)$

$\therefore U_t(x,t)=9U_{xx}(x,t)-7\left(U(x,t)+\dfrac{1}{7}\right)+1$

$U_t(x,t)=9U_{xx}(x,t)-7U(x,t)$

Of course we use separation of variables:

Let $U(x,t)=X(x)T(t)$ ,

Then $X(x)T'(t)=9X''(x)T(t)-7X(x)T(t)$

$X(x)T'(t)=(9X''(x)-7X(x))T(t)$

$\dfrac{T'(t)}{T(t)}=\dfrac{9X''(x)-7X(x)}{X(x)}=-9\pi^2s^2-7$

$\begin{cases}\dfrac{T'(t)}{T(t)}=-9\pi^2s^2-7\\X''(x)+\pi^2s^2X(x)=0\end{cases}$

$\begin{cases}T(t)=c_3(s)e^{-t(9\pi^2s^2+7)}\\X(x)=\begin{cases}c_1(s)\sin\pi xs+c_2(s)\cos\pi xs&\text{when}~s\neq0\\c_1x+c_2&\text{when}~s=0\end{cases}\end{cases}$

$\therefore u(x,t)=c_1xe^{-7t}+c_2e^{-7t}+\dfrac{1}{7}+\sum\limits_{s=0}^\infty C_3(s)e^{-t(9\pi^2s^2+7)}\sin\pi xs+\sum\limits_{s=0}^\infty C_4(s)e^{-t(9\pi^2s^2+7)}\cos\pi xs$

In fact we cannot coordinate $u(0,t)=3t+2$ and $u(1,t)=t+3$ both unless they are both belongs to constant$\times e^{-7t}$ . So this approach fails.

Approach $2$:

Apply the method in http://maths.swan.ac.uk/staff/vl/pdes-course.pdf#page=38 , i.e. let $u(x,t)=v(x,t)+3t+2+x(1-2t)$ ,

Then $u_t(x,t)=v_t(x,t)+3-2x$

$u_x(x,t)=v_x(x,t)+1-2t$

$u_{xx}(x,t)=v_{xx}(x,t)$

$\therefore v_t(x,t)+3-2x=9v_{xx}(x,t)-7(v(x,t)+3t+2+x(1-2t))+1$

$v_t(x,t)+3-2x=9v_{xx}(x,t)-7v(x,t)-21t-14+14xt-7x+1$

$v_t(x,t)-9v_{xx}(x,t)+7v(x,t)=(14t-5)x-21t-16$

with $v(0,t)=0$ , $v(1,t)=0$ and $v(x,0)=6x^2-6x$

Let $v(x,t)=\sum\limits_{s=1}^\infty C(s,t)\sin\pi xs$ so that it automatically satisfies $v(0,t)=0$ and $v(1,t)=0$ ,

Then $\sum\limits_{s=1}^\infty C_t(s,t)\sin\pi xs+9\sum\limits_{s=1}^\infty\pi^2s^2C(s,t)\sin\pi xs+7\sum\limits_{s=1}^\infty C(s,t)\sin\pi xs=(14t-5)x-21t-16$

$\sum\limits_{s=1}^\infty(C_t(s,t)+(9\pi^2s^2+7)C(s,t))\sin\pi xs=(14t-5)x-21t-16$

For $0<x<1$ ,

$\sum\limits_{s=1}^\infty(C_t(s,t)+(9\pi^2s^2+7)C(s,t))\sin\pi xs=\sum\limits_{s=1}^\infty2\int_0^1((14t-5)x-21t-16)\sin\pi sx~dx~\sin\pi xs$

$\sum\limits_{s=1}^\infty(C_t(s,t)+(9\pi^2s^2+7)C(s,t))\sin\pi xs=\sum\limits_{s=1}^\infty\dfrac{(14(-1)^s-42)t+42(-1)^s-32}{\pi s}\sin\pi xs$

$\therefore C_t(s,t)+(9\pi^2s^2+7)C(s,t)=\dfrac{(14(-1)^s-42)t+42(-1)^s-32}{\pi s}$

$(e^{(9\pi^2s^2+7)t}C(s,t))_t=\dfrac{((14(-1)^s-42)t+42(-1)^s-32)e^{(9\pi^2s^2+7)t}}{\pi s}$

$e^{(9\pi^2s^2+7)t}C(s,t)=\int\dfrac{((14(-1)^s-42)t+42(-1)^s-32)e^{(9\pi^2s^2+7)t}}{\pi s}dt$

$e^{(9\pi^2s^2+7)t}C(s,t)=F(s)+\dfrac{((14(-1)^s-42)t+42(-1)^s-32)e^{(9\pi^2s^2+7)t}}{\pi s(9\pi^2s^2+7)}-\dfrac{(14(-1)^s-42)e^{(9\pi^2s^2+7)t}}{\pi s(9\pi^2s^2+7)^2}$

$C(s,t)=F(s)e^{-t(9\pi^2s^2+7)}+\dfrac{(14(-1)^s-42)t+42(-1)^s-32}{\pi s(9\pi^2s^2+7)}-\dfrac{14(-1)^s-42}{\pi s(9\pi^2s^2+7)^2}$

$\therefore v(x,t)=\sum\limits_{s=1}^\infty\biggl(F(s)e^{-t(9\pi^2s^2+7)}+\dfrac{(14(-1)^s-42)t+42(-1)^s-32}{\pi s(9\pi^2s^2+7)}-\dfrac{14(-1)^s-42}{\pi s(9\pi^2s^2+7)^2}\biggr)\sin\pi xs$

$v(x,0)=6x^2-6x$ :

$\sum\limits_{s=1}^\infty\biggl(F(s)+\dfrac{42(-1)^s-32}{\pi s(9\pi^2s^2+7)}-\dfrac{14(-1)^s-42}{\pi s(9\pi^2s^2+7)^2}\biggr)\sin\pi xs=6x^2-6x$

$F(s)+\dfrac{42(-1)^s-32}{\pi s(9\pi^2s^2+7)}-\dfrac{14(-1)^s-42}{\pi s(9\pi^2s^2+7)^2}=2\int_0^1(6x^2-6x)\sin\pi sx~dx=\dfrac{24(-1)^s-24}{\pi^3s^3}$

$F(s)=\dfrac{24(-1)^s-24}{\pi^3s^3}-\dfrac{42(-1)^s-32}{\pi s(9\pi^2s^2+7)}+\dfrac{14(-1)^s-42}{\pi s(9\pi^2s^2+7)^2}$

$\therefore v(x,t)=\sum\limits_{s=1}^\infty\biggl(\biggl(\dfrac{24(-1)^s-24}{\pi^3s^3}-\dfrac{42(-1)^s-32}{\pi s(9\pi^2s^2+7)}+\dfrac{14(-1)^s-42}{\pi s(9\pi^2s^2+7)^2}\biggr)e^{-t(9\pi^2s^2+7)}+\dfrac{(14(-1)^s-42)t+42(-1)^s-32}{\pi s(9\pi^2s^2+7)}-\dfrac{14(-1)^s-42}{\pi s(9\pi^2s^2+7)^2}\biggr)\sin\pi xs$

Hence $u(x,t)=3t+2+x(1-2t)+\sum\limits_{s=1}^\infty\biggl(\biggl(\dfrac{24(-1)^s-24}{\pi^3s^3}-\dfrac{42(-1)^s-32}{\pi s(9\pi^2s^2+7)}+\dfrac{14(-1)^s-42}{\pi s(9\pi^2s^2+7)^2}\biggr)e^{-t(9\pi^2s^2+7)}+\dfrac{(14(-1)^s-42)t+42(-1)^s-32}{\pi s(9\pi^2s^2+7)}-\dfrac{14(-1)^s-42}{\pi s(9\pi^2s^2+7)^2}\biggr)\sin\pi xs$

share|improve this answer
    
Wow! That is a formula. –  Wok Oct 12 '12 at 23:54

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.